1985
DOI: 10.1259/0007-1285-58-687-191
|View full text |Cite
|
Sign up to set email alerts
|

Fibroadenolipoma of the breast

Abstract: Fibroadenolipoma is a well recognised but unusual benign tumour of the breast. It is a circumscribed lesion composed of fat and other breast tissues which may be normal or which may show various benign changes. The presence of smooth muscle has been recorded but was not found in our cases. A series of eight cases is described, occurring over a period of 10 years in a series of 20 000 mammograms. Radiological and pathological correlation is made and histological changes are described. Our findings are compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…Several studies (4,5,10) describe the characteristic mammographic appearance of BH as circumscribed masses composed of a mixture of fat and fibroglandular tissue. Another study (2) indicates that the characteristic mammographic appearance of these lesions is less common than previously thought and that this is due to the earlier detection of small hamartomas.…”
Section: Discussionmentioning
confidence: 90%
“…Several studies (4,5,10) describe the characteristic mammographic appearance of BH as circumscribed masses composed of a mixture of fat and fibroglandular tissue. Another study (2) indicates that the characteristic mammographic appearance of these lesions is less common than previously thought and that this is due to the earlier detection of small hamartomas.…”
Section: Discussionmentioning
confidence: 90%
“…These authors also pointed out that only a minority of cases showed the typical features of lipoma on either mammography or ultrasound. These lesions are uncommon; Crothers et al 34 recorded only eight cases in 20 000 mammograms. Haagensen 9 and Azzopardi 32 both regard this as a variant of lipoma that has incorporated epithelial elements.…”
Section: Lipomamentioning
confidence: 99%
“…35 Mammographically, they have a typical appearance of a smooth mass with a fat halo, 34 although in detail the appearances can be very variable. Clinically, they resemble lipomas, appearing as soft, circumscribed, mobile masses, which feel harder if there is a large proportion of fibrous tissue.…”
Section: Hamartoma (Adenolipoma)mentioning
confidence: 99%
“…Hamartomas, also known as fibroadenolipomas, lipofibroadenomas or adenolipomas, are composed of variable amounts of glandular, fatty and fibrous tissue 1–4 . They are uncommon benign breast tumours with an incidence of 1–4/2500 mammograms 4–7 . Seventy‐five per cent of the patients were asymptomatic, other than reporting a breast lump 8 .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] They are uncommon benign breast tumours with an incidence of 1-4/2500 mammograms. [4][5][6][7] Seventy-five per cent of the patients were asymptomatic, other than reporting a breast lump. 8 Histologically, this heterogeneous tumour has been divided into different types based on the predominance of the tissue.…”
Section: Introductionmentioning
confidence: 99%